The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11192-007-1996-1
|View full text |Cite
|
Sign up to set email alerts
|

An analysis and comparison of scientometric data between journals of physics, chemistry and engineering

Abstract: By employing the Pearson correlation, Fisher-and t-tests, the present study analyzes and compares scientometric data including number of source items, number of citations, impact factor, immediacy index, citing half-life and cited half-life, for essential journals in physics, chemistry and engineering, from SCI JCR on the Web 2002. The results of the study reveal that for all the scientometric indicators, except the cited half-life, there is no significant mean difference between physics and chemistry subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…9 For example, Tsay (2009) analyzes scientometric data between journals of physics, chemistry and engineering and finds some evidence for differences in citation behavior among scientists in these disciplines, although this comparison is restricted to a period of one year (2002). While our argument -that the difference in responsiveness to incentives across disciplines contributes to the differences in citation patterns -is surely of a cognitive origin, an evaluative approach to scientometrics would be able to offer several alternative explanations.…”
Section: Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…9 For example, Tsay (2009) analyzes scientometric data between journals of physics, chemistry and engineering and finds some evidence for differences in citation behavior among scientists in these disciplines, although this comparison is restricted to a period of one year (2002). While our argument -that the difference in responsiveness to incentives across disciplines contributes to the differences in citation patterns -is surely of a cognitive origin, an evaluative approach to scientometrics would be able to offer several alternative explanations.…”
Section: Reactivitymentioning
confidence: 99%
“…The resulting lack of diversity within the economic discipline has been studied empirically, in particular by analyzing the relative citation flows between 13 high-ranked mainstream and 13 high-ranked heterodox economic journals in two different periods: before -2008Dobusch & Kapeller 2012b) and after the recent financial and economic crisis (2009Aistleitner et al 2018). The results indicate that the monistic and closed citation behavior exhibited by (highly-ranked) mainstream economic journals remained stable after the crisis, as the mainstream journals continue to devote only minimal attention to heterodox inputs (as is evidenced by the small share of citations -less than 3% -imported from heterodox sources 13 ; see Figure 9).…”
Section: Diversitymentioning
confidence: 99%
“…Äëÿ ñòàòåé ïî ôèçèêå ýòà âåëè÷èíà ïðèáëèçè-òåëüíî ðàâíà 7 ãîäàì, ïî õèìèè è òåõíè÷åñêèì íàóêàì îêîëî 8 ëåò [18]. Ïîñêîëüêó [19], îä-íàêî ìû áóäåì îïèðàòüñÿ íà ôîðìóëó (1), ïîñêîëüêó íàñ èíòåðåñóþò âñå ñòàäèè öè-òèðîâàíèÿ ñòàòüè.…”
Section: ìîäåëüunclassified
“…Studies have investigated trends in engineering research, as shown in the publications stored in different databases for varying periods of time [3][4][5][6][7][8][9]. Some have explored the collaborative dimensions hidden in such scientific publications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%